Water hammer mitigation by internal rubber hose - Michał Kubrak (Archives of Civil Engineering, 2024)
The aim of this research was to experimentally analyse the possibility of using a rubber hose placed inside a pipeline to mitigate the water hammer phenomenon. The experiments were conducted using a steel pipeline with an inner diameter of 53 mm and an EPDM rubber hose with a diameter of 6 mm. Hydraulic transients were induced by a rapid closure of the valve located at the downstream end of the pipeline system. In order to analyse the influence of steady-state flow conditions on the maximum pressure increase, measurements were carried out for different values of initial pressure and discharge. The experimental results indicate that placing a rubber hose inside a pipeline can substantially attenuate valve-induced pressure oscillations. It was observed that the initial pressure has a significant influence on the capacity of the rubber hose to dampen the water hammer phenomenon. Comparative numerical calculations were performed using the Brunone–Vitkovský instant acceleration-based model of unsteady friction. It was demonstrated that this approach does not allow satisfactory reproduction of the observed pressure oscillations due to the viscoelastic properties of the EPDM hose used in the tests.